An interval valued intuitionistic fuzzy approach to evaluate the challenges for adopting the smart textiles in readymade garment industries: Implications for sustainable business development - MD Shafikul Islam; Saifur Rahman Tushar; Mahathir Mohammad Bappy; Mohammad Ali; Abdullah Al Nadim (Green Technologies and Sustainability, 2025)
The readymade garment (RMG) sector is critical in the economic structure of numerous developing countries including Bangladesh making up around 83% of its overall exports. Despite its significance, the sector faces substantial risks and uncertainties, including fluctuating global markets, limited product diversification, and vulnerabilities accentuated by the COVID-19 pandemic. To sustain growth and navigate global market uncertainties, the garment industry must diversify product offerings and integrate smart textiles to enhance resilience and competitiveness. However, there are significant challenges to be overcome in incorporating smart textiles into the industry to achieve sustainable business growth. This study identifies and evaluates the key challenges impeding the adoption of smart textiles in Bangladesh’s RMG sector using data obtained from a structured expert survey comprising 12 industry specialists and academicians. Employing an Interval-Valued Type 2 Intuitionistic Fuzzy (IVT2IF) integrated with Decision-Making Trial and Evaluation Laboratory (DEMATEL) methodology, the analysis highlighted “Incompatibility with current production infrastructure” with “Inadequate scalability of production” being the main cause, and “Incompatibility among the suppliers” being the most affected outcome. These findings provide actionable insights for industry stakeholders and policymakers, emphasizing strategic infrastructural investments and collaboration improvements, thus facilitating sustainable business development in the RMG sector.